2018
DOI: 10.1158/1078-0432.ccr-17-3577
|View full text |Cite
|
Sign up to set email alerts
|

Radium-223 Dichloride in Combination with Vascular Endothelial Growth Factor–Targeting Therapy in Advanced Renal Cell Carcinoma with Bone Metastases

Abstract: This study investigates the biologic activity of radium-223 with VEGF-targeted therapy in patients with advanced renal cell carcinoma (aRCC) and bone metastases. Fifteen treatment-naïve patients ( = 15) received pazopanib 800 mg orally once daily, and 15 previously treated patients received sorafenib 400 mg orally twice daily. Radium-223 55 kilobecquerel/kg was administered concurrently every 4 weeks for up to six infusions in both cohorts. The primary endpoint was decline in bone turnover markers (Procollagen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Therefore, the present study adopted the MD Anderson bone response criteria, which can be used to evaluate the treatment efficacy for bone lesions by considering the size and sclerotic changes ( 17 ). While these criteria were originally developed for evaluating bone metastases from breast cancer, they have been used in translational research to evaluate the effect of radium-223 dichloride combined with targeting therapy on bone metastases of RCC ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the present study adopted the MD Anderson bone response criteria, which can be used to evaluate the treatment efficacy for bone lesions by considering the size and sclerotic changes ( 17 ). While these criteria were originally developed for evaluating bone metastases from breast cancer, they have been used in translational research to evaluate the effect of radium-223 dichloride combined with targeting therapy on bone metastases of RCC ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hamaoka et al ( 17 ) proposed the MD Anderson bone response criteria, in which not only a size reduction, but also osteoblastic changes are considered evidence of treatment efficacy for bone lesions. These criteria were originally developed for bone metastases from breast cancer, but have been adopted during a clinical trial evaluating the efficacy of radium-223 dichloride for RCC bone metastasis ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is a retrospective analysis of imaging data prospectively collected as part of a two-cohort trial of radium-223 and anti-VEGF therapy in mRCC [15]. The trial was conducted in full concordance with Declaration of Helsinki principles and Good Clinical Practice (NCT02406521) and approved by our institutional review board.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Patients had histologically-proven renal cell cancer, ≥1 bone metastasis on imaging and non-measurable bone-only disease was allowed. Eligibility criteria, treatment data, and the safety and efficacy results of the therapeutic clinical trial have been reported [15].…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation